KEBIJAKAN HUKUM KEJAHATAN SEKSUAL DALAM LINGKUP PERGURUAN TINGGI MENURUT PERATURAN MENTERI NO 30 TAHUN 2021 TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI - Ruhol Puji Satriyo; Moh. Lubsi Tuqo Romadhan (SUPREMASI HUKUM, 2022)
Sexual crimes always develop across time and era, as well as what is felt and becomes a hot issue in these years, namely sexual crime which has begun to spread and develop among academics or among universities in Indonesia, where universities should be a strong foundation in terms of educating. generation of the nation, now Universities have only become terror and disaster for victims of sexual harassment, most of whom are students, and it is not unmitigated that the perpetrators of the crime of sexual harassment themselves are none other than him who has an important role and power, both Leaders, Lecturers, and officers and public service personnel at the Higher Education. That is why Ministerial Regulation No. 30 of 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education is here to serve as a solution and a common source of confusion for universities in Indonesia. Keywords: Legal Policy, Sexual Crime, Ministerial Regulation No. 30 of 2021